2020
DOI: 10.2754/avb202089030247
|View full text |Cite
|
Sign up to set email alerts
|

The impact of temperature-humidity index on blood morphology and β-hydroxybutyrate in different sheep breeds

Abstract: Climatic variations directly affect the animals, changing their physiology. Several factors such as species, breed, sex, age, nutrition, diseases, physiological stage, and seasonal variations can affect the pattern of haematological values. Quantitative and morphological changes in blood cells are associated with higher temperatures and humidity. Sixty-seven sheep (3 years old, not pregnant, clinically healthy) were used in the study to determine the effect of the temperature-humidity index (THI) and breed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Physiological indicators of blood are very important for farms to assess the physiological conditions of livestock and poultry ( 75 ). Seasonal change can directly affect the physiological function of animal, and its physiological indexes will change accordingly ( 19 , 76 ). Studies have reported that with the change of seasons, sheep's blood physiological indicators will also change ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological indicators of blood are very important for farms to assess the physiological conditions of livestock and poultry ( 75 ). Seasonal change can directly affect the physiological function of animal, and its physiological indexes will change accordingly ( 19 , 76 ). Studies have reported that with the change of seasons, sheep's blood physiological indicators will also change ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…The vacuum tube for blood collection contained 10% EDTA anticoagulant. The blood sample was kept at 8°C and delivered to the lab for physiological index determination right away ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies conducted under various environmental conditions have confirmed the impact of limited water availability on haematocrit levels [34][35][36]. The reduced value of the haematocrit level in Świniarka breed can be interpreted as an indicator of dehydration or anaemia during grazing in the K ąty region.…”
Section: Discussionmentioning
confidence: 93%
“…Various studies have focused on the assessment of stress and welfare in farm animals (Nečasová et al 2019;Píšťková et al 2019;Večerková et al 2019;Večerek et al 2020Večerek et al , 2021. Increasing summer temperatures present one of the stressors for livestock (Autukaite et al 2020). During the summer months, however, cattle is also exposed to another stress factor which is insect pests.…”
mentioning
confidence: 99%